Ten simple rules for developing visualization tools in genomics - Durant, Éloi; Rouard, Mathieu; Ganko, Eric; Müller, Cédric; Cleary, Allan; Farmer, Andrew D.; Conte, Matthieu; Sabot, François (2022)
Our following 10 simple rules are dedicated to biologists and bioinformaticians who, while already being at the crossroads of many fields, want to venture further into the land of Data Visualization (“datavis” or “dataviz” for short). They combine tips and advice that we would have wanted when we first started our own journeys, gathered from our experiences in building genomic and/or datavis tools, and the time spent with related communities. Additionally, they address current challenges in computational biology and the needs of the community.